PENGARUH KUALITAS PRODUK DAN PROMOSI TER HADAP KEPUTUSAN PEMBELIAN KERUPUK KULIT SAPI “CITRA SARI” DI DESA CIBURIAL KEC. CIMENYAN - Zeffanya Raphael Wijaya; Hasti Pramesti Kusnara; Cucu Hodijah (LPSDI Bina Patria, 2023)
Companies can still compete in the market if in issuing products tailored to the needs and desires of consumers, then communicating the advantages of the product to consumers. A consumer in making a decision to purchase a product can be influenced by several factors, including the quality of the product and the promotions carried out by the company. Referring to this fact, the researcher is interested in conducting research on